Barriers to university–industry collaboration in an emerging market: Firm-level evidence from Turkey - Timo Kleiner-Schaefer; Kerstin J. Schaefer (The Journal of Technology Transfer, 2022)
University-industry collaborations (UICs) are one of the main sources of external knowledge and technologies for industrial firms, particularly in the context of emerging markets (EMs) and firm development. It is thus highly relevant to identify potential barriers internal to the firm as well as in the regional innovation system that might prevent firms from using UICs for innovation, in particular in an EM context. In order to address this issue, we conduct a firm-level study of the R&D-related segment of the manufacturing industry in Istanbul. Logistic regression analysis is used to test the effect of potential barriers on using UICs for innovative activities. With this approach, we are able to identify barriers that prevent innovation-related UICs and thus form a bottleneck to collaborations in the first place. Our findings show that lack of information about UIC opportunities as well as lack of financial support for UICs are the most relevant barriers that inhibit firms' usage of UICs for innovation. This firm-level evidence points out the importance of university technology transfer offices in regional innovation systems and for fruitful UICs. We further find that administrative barriers have no significant effect, while barriers related to trust and skill matching with scientific partners even have a reverse effect to what we would have expected from the literature. This finding might point towards an effect of perceived versus deterring barriers that has been observed in innovation studies before and might be relevant for studying UICs as well.
Keywords: O30; O32; O38; 600; Innovation; Research and development; University–industry collaboration; Barrier; Emerging market; Turkey